The Effectiveness of Diabetes Medication Therapy Adherence Clinic on Glycaemic Control in Health Clinic - Alison L P, Chai (The Medical Journal of Malaysia, 2020)
In Malaysia, studies have shown that Diabetes Medication Therapy Adherence Clinic (DMTAC) in hospital settings significantly improved patients' glycaemic control and cardiovascular risk. In the review of previous studies, there were no randomised controlled trial of DMTAC done in a primary care setting – where the access to subspecialist services (endocrinologists, expensive medication, etc.) is limited. The objective of this research is to compare the glycaemic control among the uncontrolled diabetes mellitus patients between those received additional DMTAC service and those received normal clinic service in a primary care setting. The secondary objective is to investigate the common adverse outcomes of lowering HbA1c such as weight gain and severe hypoglycaemia. This was a randomized controlled study conducted in a health clinic of Sarawak. All eligible uncontrolled type 2 diabetes mellitus patients attending Kota Samarahan Health Clinic visit for at least six months before recruitment were randomly assigned to either intervention or control group (50 subjects per group). The control group received normal clinic visits with consultations by a medical officer. The intervention group, however, received four or more DMTAC visits in addition to normal clinic visits. The demographic data was collected during screening while health data including glycated haemoglobin (HbA1c) levels were collected at baseline, sixth month and one year. The main outcome for this study was HbA1c, the occurrence of severe hypoglycaemia, and weight gain. The result showed that the change in HbA1c in the intervention group (mean ± SD = -1.66 ± 2.21%) was significantly more than the control group (mean ± SD = -0.50 ± 2.21%) at 12th month (p = 0.005) with a weight mean difference of -1.16% [95% CI = -2.12, -0.21]. The regression analysis shows higher baseline HbA1c, simpler treatment plan and the intervention group yielded better HbA1c improvement. There was no difference in the BMI trend between both groups. There was no episode of severe hypoglycaemia detected among the subjects. In conclusion, the addition of DMTAC service in primary care can improve patient’s glycaemic control.